E-Marketing distribution of books by university publishers - Ali Ruziah, Abd Razak Ahmad Zainal Abidin, Mohamad Yusof Abdul Raheem, Bani Hashim Ahmad Yusairi, (N/A, 2013)
E-Marketing distribution of books by university publishers by Ali Ruziah, Abd Razak Ahmad Zainal Abidin, Mohamad Yusof Abdul Raheem, Bani Hashim Ahmad Yusairi,